(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
To develop students’ logical thinking skills and strengthen their interest in studying general education subjects through conducting small educational research, practical exercises were included in the subject curriculum. These practical exercises not only improve the quality of learning in a specific academic discipline, but also open up opportunities for interdisciplinary and scientific connections with daiyly life and increase the effectiveness of learning.